OPTC-2. Identification of enriched genes and pathways associated to hypoxia induced migration in patient-derived glioma stem cell lines by RNAseq. (5th July 2021) - Hanon, Olivia Morris; Mahmoud, Yamil; Vera, Mariana; Girotti, Romina; Rabinovich, Gabriel; Sevlever, Gustavo; Scassa, Maria Elida; Richardson, Guillermo Videla
Abstract: Glioblastomas (GBM), the most prevalent and lethal primary brain tumors, are characterized by high intertumoral heterogeneity, diffuse infiltration, and resistance to conventional therapies. Notably, the ability of tumor cells to invade surrounding tissues is one of their most damaging characteristics, it not only causes resistance to therapies such as surgery and radiotherapy but is ultimately the primary cause of death. Therapies that cause hypoxia (e.g. anti-angiogenic therapies) have been shown to increase invasiveness, leading to resistance to the therapy itself and further complications for the patients. Using patient-derived glioma stem cell lines (GSCL) we have discovered cell lines that display heterogeneous migratory behavior in response to hypoxia. As expected we observed that four GSCLs studied had increased migration in hypoxia. Strikingly, two other cell lines studied showed decreased migration in hypoxia. This unforeseen result reflects the heterogeneous nature of GBM and the difference between these GSCLs could be key to understanding this variable. To delve into the molecular context that could explain these differences we performed an exploratory RNAseq analysis on four of the GSCLs, two that showed hypoxia-induced migration and two with decreased migration in hypoxia, and evaluated genes differentially expressed in hypoxia versus normoxia. We also carried out gene ontology and pathway enrichment analysis to discover molecular and pathway patterns consistent with the migratory behaviors observed in each group of GSCLs. The results show how that a similar migratory response to hypoxia coincides with particular sets of enriched genes and pathways. Specifically, we found NOTCH and WNT signaling pathways upregulated in GSCLs which showed increased migration in hypoxia while the IFN-gamma pathway upregulated in GSCLs with decreased migration in hypoxia. Knowing the individual molecular mechanisms responsible for the migratory behavior could allow for tailor-made therapies that reduce the dissemination of these tumors.